Student Sports As A Factor of Training of Athletes of Higher Achievements - Roziya, Alimbaeva (International Journal of Psychosocial Rehabilitation, 2020)
The modern stage in the development of student sports in Uzbekistan is characterized by the emergence of new tasks of physical education in universities. The organization of sports training for students in universities is properly scientifically undeveloped and not systematized. In the conditions of commercialization and professionalization of sports, universities that provide the opportunity to obtain higher professional education are not only guarantors of securing highly qualified athletes in the region but also maintainers of the system of sports training. The article outlines the general characteristics of sports of the highest achievements, including among student sports teams; the system of organization and the dynamics of the results of student sports teams are analyzed; and recommendations aimed at modernizing the existing organization system have been developed.